Sieve element traits differ in pulvini and petioles of Mimosa (Leguminosae, Caesalpinioideae) with different types of leaf movement - Silva, Stefany Cristina de Melo; Machado, Silvia Rodrigues; Rodrigues, Tatiane Maria (Canadian Science Publishing, 2024)
The vascular system, particularly the phloem, has been considered a key issue in driving the pulvini functioning. Studies comparing phloem in different leaf regions and in plants with different leaf movement types can help clarifying the aspects involved in the pulvini functioning. Here, we investigated the morphological traits of the sieve tube elements in a comparative way between pulvini and petioles of Mimosa pudica L. (a legume with fast leaf movements) and Mimosa caesalpiniifolia Benth. (a legume with slow leaf movements). Pulvini and petioles were analyzed under light and transmission electron microscopy. Sieve elements in pulvini had thicker walls than those of petioles, especially in M. pudica. Nacreous walls occurred in the sieve elements of M. pudica pulvini. Dispersive and non-dispersive P-proteins and P-plastids occurred in the pulvini and petioles of both species. The marked differences in the lumen area and cell wall features of the sieve elements between pulvini and petiole indicate the specialization of the phloem in the pulvinus functioning.